Optimal monetary policy response to endogenous oil price fluctuations - Arnoud Stevens (National Bank of Belgium, 2015)
Should the central bank seek to identify the underlying causes of oil price hikes in determining appropriate policy responses to them? Most likely not. Within a calibrated new-Keynesian model of Oil-Importing and Oil-Producing Countries, I derive the Ramsey policy and analyze optimal monetary policy responses to different sources of oil price fluctuations. I find that oil-specific demand and supply shocks call for similar policy responses, given the low substitutability of oil in production and the incompleteness of international asset markets.
Keywords: E52; E61; Q43; 330; Oil Prices; Optimal Monetary Policy; Ramsey Approach; Welfare Analysis; Ölpreis; Schock; Geldpolitik; Wohlfahrtsanalyse